Biocatalytic Potential of a Raoultella terrigena-Derived Lipolytic Enzyme for High-Performance Detergents - Mfezeko Noxhaka; Nonso E. Nnolim; Lindelwa Mpaka; Uchechukwu U. Nwodo (Fermentation)
Dump sites harbour microorganisms with potential for environmentally friendly industrial applications. This study assessed the lipolytic activity of municipal dumpsite-associated bacteria and evaluated the stability of the most potent isolate’s lipolytic enzyme against laundry detergents. It also examined the crude lipase’s ability to remove stains from cotton fabric. Among twelve bacteria isolated, five demonstrated notable halo zones on tributyrin agar plates. The diameters (mm) were MN38 (11 ± 1.4), MN1310 (8.5 ± 0.7), MN28 (6.5 ± 0.71), MN18 (7.0 ± 1.4), and MN310 (8.15 ± 0.21). Quantitative analysis revealed that MN38 exhibited the highest lipase activity (14.76 ± 0.27 U/mL), while MN1310 showed the lowest (6.40 ± 0.85 U/mL). Nucleotide sequence analysis identified the isolates as Raoultella terrigena veli18 (MN38), Stenotrophomonas maltophilia veli96 (MN1310), Viridibacillus sp. veli10 (MN28), Stenotrophomonas sp. veli19 (MN18), and Klebsiella sp. veli70 (MN310). The crude lipase from R. terrigena veli18 maintained 73.33%, 52.67%, 55.0%, and 54.0% of its original activity after 60 min of exposure to Sunlight, Surf, Maq, and Omo, respectively. Adding crude lipase to enzyme-free laundry detergents significantly enhanced their cleaning efficacy, completely removing oil stains from cotton fabric. This performance of R. terrigena veli18 crude lipase highlights its potential as an effective detergent bio-additive.